Prevalence and characterization of extended spectrum beta-lactamase-producing Enterobacter cloacae strains in Algeria - Nedjai, Sabrina; Barguigua, Abouddihaj; Djahmi, Nassima; Jamali, Loubna; Zerouali, Khalid; Dekhil, Mazouz; Timinouni, Mohammed (The Journal of Infection in Developing Countries, 2013)
Introduction: Expended spectrum β-lactamase (ESBL)-producing Enterobacter cloacae is an important nosocomial pathogen. In this study, the prevalence and the molecular epidemiology of ESBL producing E. cloacae strains isolated from various hospitals in Annaba, Algeria were investigated. Methodology: The study involved 63 isolates of E. cloacae obtained during 2009 at the four hospitals in Annaba. The detection of ESBL was performed using the double-disk synergy test and the combined disk test. Minimum inhibitory concentrations (MICs) were determined using the agar dilution method. The presence of blaCTX-M, blaSHV, blaTEM, and blaDHA β-lactamase genes was evaluated by PCR, and genomic typing was determined by pulsed-field gel electrophoresis (PFGE) analysis. The clinical and microbiological data were entered into the EpiI Info database. Results: Thirty isolates (47.6%) had an ESBL phenotype. BlaCTX-M group1 (76%); blaTEM (70%) were the most prevalent, followed by blaDHA (16.6%) and blaSHV (10%). Eighteen strains expressed at least two bla genes. MICs revealed a high level of resistance to cefotaxime, ceftazidime, and cefepime. PFGE revealed an epidemic clonal dissemination of these isolates. Various risk factors associated with the occurrence of ESBL-producing E. cloacae were detected. Conclusions: A higher frequency of ESBL-producing isolates and a diversity of β-lactamases were detected among ESBL-producing E. cloacae; these resulted from an epidemic clonal dissemination and high transference of ESBL genes between bacteria in hospital settings. Strict measures will be required to control the further spread of these pathogens in hospital settings.